Outcomes of pregnancy in Wilson’s disease: a population-based study from multiple centres of the Han population in China - Rao, Rao; Yu, Xu-En; Zhou, Zhi-Hua; Shu, Shan; Du, Yi-Gang; Han, Yong-Zhu; Han, Yong-Sheng (Frontiers in Medicine, 2024)
Objectives: Wilson′s disease is an autosomal recessive disorder related to copper metabolism which mostly patients occurs in adolescents, fertility has become a problem that WD needs to face.Methods: A twenty-one years retrospective follow up study was conducted to identify patients with outcomes of pregnancy. Results: Untreated female patients with WD had a spontaneous abortion rate of 44%.Notably, urinary copper levels below 616 μg/24H were strongly associated with successful pregnancy. The nomogram built on these variables were age, urinary copper, haemoglobin and Child-Pugh classification, internally validated and showed good performance.The spontaneous abortion rate was 44 % in untreated females with WD and developed a four-variable risk prediction model to accurately predict the likelihood of a successful pregnancy.